New Aspects of ZZ Transform to Fractional Operators With Mittag-Leffler Kernel - Jena, Rajarama Mohan; Chakraverty, Snehashish; Baleanu, Dumitru; Alqurashi, Maysaa M. (Frontiers in Physics, 2020)
Recently, it was introduced a new integral transform viz. ZZ transform which generalizes the Laplace and Aboodh integral transforms. In this paper, we have addressed the relationship among the ZZ transform with Laplace and Aboodh transforms. Further, the ZZ transform is applied to the fractional derivative with Mittag-Leffler kernel defined in both the Caputo and Riemann-Liouville sense. In order to illustrate the validity and applicability of the transform, we have solved some illustrative examples.